1999
DOI: 10.1046/j.1570-7458.1999.00588.x
|View full text |Cite
|
Sign up to set email alerts
|

The spatial and temporal distribution of the grain aphid Sitobion avenae in winter wheat

Abstract: The spatial and temporal distribution of the grain aphid Sitobion avenae F. (Homoptera: Aphididae) was studied within a field of winter wheat during the summer of 1996. Sampling was done using four nested grids comprising 133 locations. Analysis by Taylor's power law gave results typical for insect populations. Analysis by SADIE (Spatial Analysis by Distance Indices) showed spatial pattern due to edge effects and sampling scale, and positive but mild spatial association, although spatial patterns were ephemera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
61
0
6

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 29 publications
(36 reference statements)
8
61
0
6
Order By: Relevance
“…Another large-scale spatial distribution study of common farmland arthropods in winter wheat fields also demonstrated higher density of species along edges . The studies by Winder et al (1999) and Holland et al (1999) noted the effervescent occurrence of edge-biased distributions. These findings agree with Wilson and Morton (1993) who showed that edgebiased distribution of two-spotted spider mite, Tetranychus urticae Koch (Acari: Tetranychidae), in cotton was only prominent early in the growing season but eventually diminished as the season progressed.…”
Section: Edge-biased Distributions In Open Field Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another large-scale spatial distribution study of common farmland arthropods in winter wheat fields also demonstrated higher density of species along edges . The studies by Winder et al (1999) and Holland et al (1999) noted the effervescent occurrence of edge-biased distributions. These findings agree with Wilson and Morton (1993) who showed that edgebiased distribution of two-spotted spider mite, Tetranychus urticae Koch (Acari: Tetranychidae), in cotton was only prominent early in the growing season but eventually diminished as the season progressed.…”
Section: Edge-biased Distributions In Open Field Systemsmentioning
confidence: 99%
“…The author noted that the onset of infestations by black bean aphids was near field edges and eventually spread throughout the field, although field edges would be the areas with the highest aphid density. Winder et al (1999) conducted a large-scale study of the effect of grid size on the analysis of the spatial distribution of English grain aphids, Sitobion avenae Fabricius (Hemiptera: Aphididae) and found that significant edge effect was detected for large grid size with higher count of aphids along field edges. However, the edge-biased distribution was not evident at small grid sizes.…”
Section: Edge-biased Distributions In Open Field Systemsmentioning
confidence: 99%
“…Nematollahi et al (2014) did, however, recognize the need to stratify fields to reduce variability. Edge effect spatial patterns of arthropods in field crops and their importance within sampling plans has been identified in many arthropod species (Cusson et al 1990, Winder et al 1999, Ferguson et al 2003. Edge effects in large fields typically result in zero-inflated data sets wherein most data points, which are positioned in the field interior, contain few or no detectable cabbage aphid populations.…”
Section: Discussionmentioning
confidence: 99%
“…Many arthropod pests, including aphids, have exhibited aggregated spatial distributions (Trumble 1982, Feng and Nowierski 1992, Powell et al 2006, which are caused by factors such as land topography (Hill and Mayo 1980), distance from crop edge (Winder et al 1999, Nansen et al 2005, and plant phenology, including growth stage (Ferguson et al 2003) and leaf age (Kennedy and Booth 1951). This information may be useful in reducing sampling effort and increasing sampling accuracy for emerging infestations of arthropods in broad-scale fields, wherein sampling is targeted toward plant parts and field regions where the arthropods are most likely to occur.…”
mentioning
confidence: 99%
“…Podaci iz literature nisu brojni, ali ukazuju da postoji značajna varijabilnost u rasporedu biljnih vašiju u polju. Tako na primer, prema studijama Winder et al (1999) i Al Hassan et al (2013), biljne vaši su brojnije u ivičnoj zoni polja, dok su prema Ruggle & Holst (1995), Bowie et al(1999) i Fievet et al (2007 brojnije u centru ili pak ne postoji nikakav očigledni obrazac njihove distribucije (Winder et al, 2005).…”
Section: Uticaj Različitog Karaktera Ivične Zone Polja Na Model Sisteunclassified